(untitled) (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2024)
Objective: To describe the case of a patient with anal atresia. Introduction: Imperforate anus or anal atresia is a congenital anorectal malformation in which there is no normal anal opening at birth. Approximately half of the patients with anal atresia also have anomalies in other organ systems. Late diagnosis can occur in one out of every five newborns, despite routine postnatal evaluation. Such delay can increase morbidity and mortality. Case Report: A 2 months and 15 days old female patient, accompanied by her mother, presented for her first checkup at a Type A health center in a rural community. Discussion: In this patient, it is important to highlight that she had not received any medical attention until she came to our health center at almost 3 months old. During the physical examination, the absence of an anus and the passage of feces through the vagina (cloaca) were evident. While it is true that late diagnosis can occur in one out of every five newborns, in this patient, the delay was over 2 months, for which we could not find similar cases in the literature.